The Teaching Chinese Folk Song Singing Ornaments in Jianghan Plain of China - Yarong, Ran; Pattananon, Nicha; Ngamsutti, Chalermpon (Journal of Modern Learning Development, 2023)
The ornaments of Chinese folk songs are mostly used to enrich the music to add its characteristics and effects. The ornaments' training skills in vocal music singing are mainly reflected in the continuous sound, arpeggios, jumping sound, slip sound, tonic sound, and several other ornaments. In the long-term development process of Chinese national vocal music art, "embellish cavity" has formed a set of unique singing techniques which embellish, ornament, and beautify the singing style. It can be seen that a singing skill of Chinese characteristics is applied to the singing skill of song ornaments. However, the people created and spread folk songs orally, so there was no fixed way of recording music at the beginning. These rich ornaments just survived in the minds of the singers and were passed down from generation to generation through the mouth. This article presented the teaching Chinese folk sing singing ornament in Jianghan plain in China.